Entrepreneurship and Economic Development: Theory, Evidence and Policy - Wim A. Naudé (Institute for the Study of Labor (IZA), 2013)
This paper provides an overview of the state of the art of the intersection of development economics and entrepreneurship. Given the relative neglect of entrepreneurship by development scholars it deals with (i) recent theoretical insights from the intersection of entrepreneurship and development studies; (ii) the empirical evidence on the relationship between entrepreneurship and development; and (iii) fresh insights for entrepreneurship policy for development that emerges from recent advanced in this area, including female entrepreneurship in developing countries.
Keywords: M13; O10; O17; O40; 330; entrepreneurship; development; small business; private sector development; innovation; business